Lecturers and students' perception of factors influencing school dropout among undergraduates in the university of Ibadan (2015)
This study investigated factors responsible for undergraduate dropouts in the University of Ibadan. The samples of the study were 150 students of the faculty of science and college of medicine (M = 64, F = 86) and 50 faculty of science and college of medicine lecturers (M 35 F 15) selected through simple random sampling technique. Two questionnaires developed by the researcher: Student perception of school dropouts’ questionnaire (SPSDQ) and lecturer perception about school dropout questionnaire (LPSDQ) were used to collect data from the respondents. Data collected was analysed using descriptive statistics of percentages, mean and standard deviation. Findings of the research revealed that Faculty of science students have the following averages for the dependent variables: (misconduct 54%; crime 61% and Academic failure 83%); college of medicine revealed the following averages for the variables (Misconduct - Nil; crime - Nil and academic failure - 77%) faculty of science lecturers revealed the following for dependent variables: (misconduct - 60% crime - 70% academic factors - 81%) and college of medicine lecturers revealed (misconduct - Nil; Crime - Nil and Academic factors - 69%). The study recommended that all stakeholders should combat dropout syndrome among undergraduate students.